Acesso à informação para usuários com deficiência visual em bibliotecas públicas de João Pessoa: realidade e desafios - Santos, Ana Lúcia Leite (2023)
It addresses inclusive practices for visually impaired users in public libraries in João Pessoa, in order to understand their reality and challenges. With the general objective: to analyze the inclusion of people with visual impairments, through the products and services provided by public libraries in the city of João Pessoa, Paraíba. And as specific objectives: to identify in the Public Libraries of João Pessoa, Paraíba, the physical accessibility of the collection and the attitudinal accessibility of the servers of the collection, verifying if there is training of librarians and assistants in the orientation regarding the use of accessibility equipment; map in the scientific and technical literature the policies, equipment and instruments to support the care of visually impaired users; and contribute to the discussion about access to information for visually impaired users in public libraries. Investigating the challenges of socio-environmental spaces, products and services provided by the three libraries registered as public in the city of João Pessoa, with the National System of Public Libraries (SNBP): the Augusto dos Anjos Library; the Juarez da Gama Batista Library and the Dumerval Trigueiro Mendes Library. Methodologically, we sought to develop an exploratory-descriptive research, according to its objectives, based on data collection. The investigation was characterized by a qualitative approach, of a descriptive nature, constituting itself as field research. With an emphasis on the results regarding the investigated reality, we used applied research, the techniques and instruments employed for data collection, and the analysis procedures used were: bibliographical research, documental research and participant research, as support for the formation of the theoretical framework. Data collection was carried out in two stages: the first through a bibliographical survey on the three libraries, the second, a field research was carried out, proceeding with visits to the libraries for the application of a questionnaire and participant observation. The questionnaire was applied with the coordinating librarians of the researched public libraries. The contributions guided the way to answer the following research question: How to create the necessary conditions for visually impaired users to access information in public libraries in the city of João Pessoa? This time, the data from the questionnaires were analyzed and helped to answer the research question and meet the proposed objectives. From the scenario reflected, the research reveals that the three public libraries in the city of João Pessoa, currently need better structures to serve users with visual impairments. It is believed that such contingencies can be resolved or at least mitigated through the development of accessibility practices ensured by the Brazilian legal framework and through some recommendations contained in this study. Therefore, we learn from this research that there have been significant advances in relation to the legal framework, with regard to the inclusion and accessibility of visually impaired users in public libraries in Brazil. However, in terms of access conditions, progress is still practically non-existent. Breaking barriers, especially attitudinal ones, predicting and providing accessibility conditions, both physical, communicational and informational, and creating alternatives to avoid excluding attitudes, requires that laws be put into practice, investments in actions, in adequate materials, in qualification, in architectural adequacy and, mainly, in investments in praxis, which combat inappropriate and prejudiced attitudes.